Data Architecture - Tengku Affina Nur Jannah (STIKes Ibnu Sina Ajibarang, 2025)
Data architecture is a framework that structures and manages data flows in an organization so that they can be used optimally to support data-based decision-making processes. The right design in data architecture ensures that data can be stored, accessed, processed, and analyzed efficiently. The main components in data architecture include data sources, storage systems, data processing, data integration, and analytics. In addition, aspects of security and data quality management also play an important role in maintaining data integrity and confidentiality. In the context of an ever-evolving business, data architecture must be able to adapt to changing organizational needs and existing technologies, as well as provide scalable and flexible solutions. Therefore, good data architecture management is a key factor in achieving operational efficiency and competitive advantage in the digital era.